TEKNOLOGI CLOUD ACCOUNTING SOFTWARE DALAM PENGOLAHAN TRANSAKSI KEUANGAN USAHA KECIL MENENGAH - Rahmawati, - (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Small and Medium Enterprises have a high enough role in improving economic growth in Indonesia. A total of 97% of the workforce can be absorbed by the Small and Medium Enterprises. The increasing presence of SMEs, there arises a problem in the management of financial transactions. SMEs have minimal knowledge in managing their business. With the sober knowledge, resulting in less innovation SMEs in generating product, so it has limited working capital, as well as the lack of expertise and knowledge in developing their business. Cloud Accounting Software comes as accounting software that uses cloud technology to financial management. Where the use of web-based applications that users can access via the Internet using a user and password. This technology makes it easy for users in terms of access anytime anywhere without having to install the program. For SMEs that have solid daily transactions, the technology is suitable to be applied to get the ease of viewing the report. Every transaction that is processed by the user will be directly saved automatically establishes a report. Which is expected to help SMEs to create, read, and manage their financial statements. With so owners can get information and make decisions quickly on most goods and less desirable than traded goods as well as the financial condition of the company for the lending of capital as well as other interests.Keywords: Cloud Accounting Software, Web Based, Financial Transactions Processing, SMEs.